1997
DOI: 10.1038/sj.onc.1200828
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic activation of c-Myb by carboxyl-terminal truncation leads to decreased proteolysis by the ubiquitin-26S proteasome pathway

Abstract: c-myb activation by insertional mutagenesis in murine myeloid leukemias can lead to amino (NH 2 )-terminal or carboxyl (COOH)-terminal truncation of its protein product. We observed that in these leukemias, the steady state level of the protein truncated at the COOH terminus was remarkably higher than that of the protein truncated at the NH 2 -terminus or full length wild-type protein. To examine the rate of proteolysis of di erent forms of Myb in a uniform cellular background, the proteins were constitutively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 27 publications
1
61
0
Order By: Relevance
“…Several phosphorylation sites have been demonstrated in the N-and C-termini of c-Myb, and some of these sites seem to be functionally important (Aziz et al, 1995;Miglarese et al, 1996). Furthermore, the deletion of the C-terminal region including PEST sequences increased the protein stability (Bies and Wol , 1997). These ®ndings suggest that posttranslational modi®ca-tion of the C-terminus, such as phosphorylation or degradation, plays a critical role in the regulation of cMyb function.…”
Section: Introductionmentioning
confidence: 94%
“…Several phosphorylation sites have been demonstrated in the N-and C-termini of c-Myb, and some of these sites seem to be functionally important (Aziz et al, 1995;Miglarese et al, 1996). Furthermore, the deletion of the C-terminal region including PEST sequences increased the protein stability (Bies and Wol , 1997). These ®ndings suggest that posttranslational modi®ca-tion of the C-terminus, such as phosphorylation or degradation, plays a critical role in the regulation of cMyb function.…”
Section: Introductionmentioning
confidence: 94%
“…16,21). Although the mechanism of negative regulation by the NRD is not fully understood, it is likely to act through multiple mechanisms including interaction with other proteins (22)(23)(24), intramolecular interactions (25), and effects on protein stability (26).…”
Section: Introductionmentioning
confidence: 99%
“…c-Myb is also regulated by post-transcriptional modifications including sumoylation, phosphorylation, ubiquitination, and acetylation [177][178][179][180][181][182][183]. These modifications lead to changes in c-Myb stability, DNA-binding activity and transcriptional transactivating activity.…”
Section: C-mybmentioning
confidence: 99%
“…In addition, it was recently reported that phosphorylation of Thr354, Thr486, Ser556, and Thr572 in the NRD by p38MAPK in response to stress led to proteasomal degradation of c-Myb [183]. The proteasome is targeted to the NRD, through ubiquitination which occurs at an undefined lysine residue(s) in the NRD [180,185]. Thr572 is also targeted for phosphorylation by glycogen synthase kinase 3 (GSK3) which recruits E3 ubiquitin ligase Fbw7 leading to degradation of c-Myb [186].…”
Section: C-mybmentioning
confidence: 99%
See 1 more Smart Citation